The Effect of Foot and Hand Massage on Pain Reduction in Post Caesarea Sectio Patients in Rajawali Room 2 Banten Regional General Hospital 2024 - Neng Yeni; Cucu Nurhasanah; Meynur Rohmah; Denida Mahasari (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Sectio caesarea is a surgical procedure on the abdominal wall and uterus which aims to give birth to a child. Indications that do not support a mother having a normal delivery are narrow pelvis, experiencing pre-eclampsia, premature rupture of membranes and several other factors. The World Health Organization (WHO) predicts that deliveries by caesarea sectio account for 10% to 15% of all births. The sensation of labor pain can be treated pharmacologically and non-pharmacologically. There are various ways to treat pain in post partum mothers using SC procedures, one of which is the foot hand technique massage, where stimulation is given by massaging the soles of the feet and hands. The aim of this community service is to determine the effect of Foot Hand Massage on pain in after sectio caesarea. The method used is a quantitative method with quasi experiment a sample of 30 people, one group pre-test and post-test. The instrument used is the Numeric Rating Scale (NRS). Data were analyzed using the Wilcoxon test. The results show data before being given the Foot technique Hand Massage has a pain scale of mild to moderate, whereas after being given the Foot Hand Massage technique it has a scale of mild to no pain, and the p value = 0.000 is obtained, so it is concluded that there is an influence of the Foot Hand Massage technique on the level of pain in clients post caesarea sectio surgery.